Peningkatan Kualitas dan Kuantitas Produk Media Pembelajaran dan Alat Peraga Edukatif dari Daur Ulang Limbah Plastik - Siti Halimatus Sakdiyah; Hena Dian Ayu; Anggri Sartika Wiguna (Abdimas Pedagogi: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
Abstract: Malang City faces a significant plastic waste problem, reaching 65,921 tons per day, while the demand for educational media continues to grow due to its status as an educational hub. CV. Wijaya Multi Guna, a small-scale industry in Malang producing educational teaching aids from recycled plastic waste, encounters challenges in production capacity, limited product variation, and conventional marketing methods. This community service program aims to enhance the quality and quantity of the partner's products through a Participatory Learning and Action approach. Methods employed include socialization, training, mentoring, technology implementation, and evaluation. The results demonstrate a 50% increase in production capacity, from 1,000 kg to 1,500 kg per month, along with an expansion of product variants from two to five types. Additionally, digital marketing training successfully broadened the marketing reach to the national level. In terms of business management, a more transparent financial recording system was implemented, and a more professional division of labor among workers was established. The application of technology and innovation has significantly improved the competitiveness of the partner's products in the national market and created opportunities for future business sustainability. Abstrak: Kota Malang menghadapi masalah sampah plastik yang signifikan, sementara kebutuhan media pembelajaran terus meningkat. CV. Wijaya Multi Guna, yang memproduksi alat peraga edukatif berbasis daur ulang limbah plastik, mengalami keterbatasan dalam kapasitas produksi, variasi produk, serta pemasaran. Program pengabdian ini bertujuan untuk meningkatkan kualitas dan kuantitas produksi mitra menggunakan pendekatan Participatory Learning and Action. Metode yang diterapkan mencakup sosialisasi, pelatihan, pendampingan, penerapan teknologi, serta evaluasi. Hasil menunjukkan peningkatan kapasitas produksi hingga 50%, dari 1000 kg menjadi 1500 kg per bulan, serta penambahan varian produk dari dua jenis menjadi lima jenis. Selain itu, program ini berhasil mengembangkan strategi pemasaran digital, yang memperluas jangkauan pemasaran hingga tingkat nasional. Pada aspek manajemen usaha, diterapkan sistem pencatatan keuangan yang lebih transparan dan pembagian tugas yang lebih profesional di kalangan pekerja. Penerapan teknologi dan inovasi ini berhasil meningkatkan daya saing produk mitra di pasar nasional, serta menciptakan peluang keberlanjutan usaha di masa mendatang.